A Study on Gravimeteric Situation in East of Uromieh Lake Region with Determination of Suitable Bouguer Density - Bayat, Maryam; Teymoorian, Asghar (International Journal of Geography and Geology, 2015)
In this paper, the optimal density determined using fractal geometry to Urmia region in this way trying to minimize the topography of the region. Using this method, we can obtain the Bouguer anomaly optimum density east of Uromieh Lake and turn to the regional gravitation.